Rate of Infiltration under Different forest Covers of Garhwal Himalaya - Nazir, Tahir; Sharma, C. M. (Indian Forester, 2015)
In a forest environment, hydraulic conductivity varies by surface condition which is a function of the type and severity of disturbance. The present study was conducted in five forest covers of Garhwal Himalaya i.e Pinus roxburghii, Cedrus deodara, Quercus leucotricophora, Abies pindrow and moist mixed temperate deciduous forest. The infiltration rate was estimated under the disturbed and undisturbed forest covers, by the double ring infiltrometer method. The infiltration rate after 5 minutes was maximum in Pinus roxburghii forest 51.20±3.01cm/hr, followed by Cedrus deodara forest (41.20±1.38cm/hr), Quercus leucotrichophora forest (34.00±3.46cm/hr), Abies pindrow forest (32.00±3.46cm/hr), and moist mixed temperate deciduous forest (27.2±3.01cm/hr). The infiltration rate after 445 minutes was maximum under Quercus leucotrichophora (8.53±0.17cm/hr), followed by moist mixed temperate deciduous forest (8.51±0.54cm/hr), Pinus roxburghii forest (2.50±0.45cm/hr), Abies pindrow forest (2.17±0.16cm/hr) and Cedrus deodara forest (0.33±0.00cm/hr). The higher rate of infiltration in an undisturbed forest is attributed to thicker layer of humus. Therefore, undisturbed forests contributed more to the ground water table than the disturbed forests.